Eles amam viajar: um estudo sobre os turistas Wanderlust, utilizando Grounded Theory e modelo 3M de motivação e personalidade - Gisele de Araujo Pereira (2015)
Tourism has been consolidated as one of the most important economic activities of today, with growth forecast to reach ever higher levels (UNWTO, 2013; DIAS; CASSAR, 2005; Swarbrooke; HORNER, 2002). Associated with economic, social, political and cultural changes that have allowed the growth of tourism demand, seems to be a phenomenon related to the intensification of travellersexpectations, referring to a strong and continuing affective and cognitive trend of active and passive involvement with travel. This intense desire to travel, known in German as wanderlust, is the focus of this work. Seeking to investigate characteristics inherent to the tourists wanderlust typology from the exploration of the relationship between personality, motivation and behavior, this study was conducted in two stages. The first, qualitative, was conducted through in-depth interviews with 16 travelers. The second, quantitative, was realized through the application of a survey supported by 3M Model of Motivation and Personality (Mowen, 2000). The qualitative data analysis was performed using Grounded Theory and Content Analysis techniques. Quantitative data were analyzed based on structural equation modeling, through the Partial Least Squares (PLS) technique, using the strategy of models development (Hair et al., 2009). The two phases were joined, and the results of the qualitative phase strongly contributed to the development of quantitative phase. In the qualitative phase, a scheme was developed with the main elements that make up the universe of wanderlusters: a) elements that form the wanderlusters; b) elements that motivate wanderlusters; c) recurring behaviors of wanderlusters; d) alternative activities to travel practiced by wanderlusters. In the qualitative phase, elements that motivate wanderlusters were added to some personality traits of the 3M Model and thus, at the quantitative phase, six different model combinations were tested. The final chosen model presented a mix of formative and reflective constructs and the motives identified in the qualitative phase were divided between push/antecedents of wanderlust - search for self-knowledge and personal development, search for authenticity and freedom and break the routine and escape from reality -; and pull/consequents of wanderlust - experience the cultural diversity, experience adventures and challenges, living news and have stories to tell. The latter were also antecedentes of frequent traveler construct. Research has shown that the wanderlust tourist is, first of all, a tourist and that their desires and motivations do not differ much from motivations already raised about consumer behavior in tourism. Although several of the motivations identified in the qualitative phase have already been portrayed by other studies, this research allowed for a cut focusing on the motivations and personality traits more directly related to wanderlusters. Among the findings, we can highlight the trace of romanticism as the personality trait that best showed wanderlust prediction and need for fun as the best predictor of frequent traveler. Still, experience adventures and challenges was the superficial motive that received the greatest impact of wanderlust and provided the biggest impact on frequent traveler. Wanderlust already shown to have a great relationship with the superficial motives: seek novelty, experience adventures and challenges, experience the cultural diversity and have stories to tell. However, self-efficacy was not a good trait compound to evaluate the behavior of wanderlusters. For the academy, the research contributes to the development of 3M model once it investigate an untapped behavior and proposing the addition of the reasons push and pull at different levels of the model. Still, this research brings a innovation by performing the 3M Model evaluation using Partial Least Squares and realizing a comparative analysis between reflective and formative ways of constructs operationalization.